Analisis Pembatalan Pesanan di Platform Shopee Menggunakan Seven Tools: Studi Kasus pada UMKM Puntang Coffee - Manthiq, Hanif; Pardian, Pandi (Universitas Galuh, 2025)
Although e-commerce makes it easier for businesses to expand their markets, this convenience allows buyers to easily cancel orders, disrupting MSME operations. This research aims to analyze the main causes of order cancellations at the Puntang Coffee store on the Shopee platform and to formulate control proposals. This study uses a qualitative case study method, with data analyzed descriptively via the Seven Tools approach. The Pareto analysis shows that the dominant causes of cancellation are